Optimalisasi Fungsi Pengawasan Dewan Etik Mahkamah Konstitusi - Jurdi, Fajlurrahman; Hanapi, Rizqa Ananda; Hidayat, Taufik (Jurnal Hukum & Pembangunan, 2020)
Violations of law and code of ethics performed by the constitutional judge shows that there is abuse of power within the court. The existence of Board of Ethics has questioned due to these violation and accused for not being able to perform its function in maintaining the dignity of the court. This concludes that the optimization of the function of the Board of Ethics are necessary. This is a normative and doctrinal research with several approaches. This research explains that board of ethics needs several changes within its body, such as: 1) boarden the board’s authority from investigating reports and allegations of violation, to performing fact-findings and tracing the indications of violation; 2) adding staffs to support the board; and 3) regulating the board and the structure under The Law on Mahkamah Konstitusi.